The degree of delegation of authority to the principals of basic and secondary schools in the Kasbah of Mafraq district from the point of view of teachers - Al-Zyoud, Ahmed Khalaf Mohammed (Journal of Educational and Psychological Sciences, 2022)
The study aimed to reveal the degree of authority delegated to secondary school principals in Kasbah Al-Mafraq District and its relationship to organizational commitment from the teachers' point of view. The study reached the following results: The degree of delegation of authority for school principals of the Directorate of Education in Mafraq Governorate was at a high level, and the results of the study indicated that there were no statistically significant differences in the degree of delegation of authority due to the effect of the variable gender, educational qualification, and years of experience on all fields. In light of the results of the study, the study recommends a set of recommendations, the most important of which are: Follow the democratic approach It is based on delegation of authority, encouraging teachers to take responsibility and collective participation in decision-making, which contributes to enhancing the level of organizational commitment among teachers.
Keywords: delegation of authority; secondary school principals; Mafraq district